Analisis Penerimaan Pajak Penghasilan (PPH) Pasal 21 Selama Masa Pandemi Covid-19 - Yagi, Gika Lukistrianti (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2024)
Based on the Realization of State Revenue and Expenditure Budget period 2020 - 2022, the tax sector remains the highest source of state revenue. In the State's efforts to continue to increase State revenues, there are major events that must be faced by almost the entire world, including Indonesia. Corona Virus Disease 2019 (COVID-19) has become a world pandemic that poses various risks. In an effort to recover revenues in the tax sector, particularly Tax Article 21 revenues, there have been several important rules or policies, such as tax incentives, progressive tariff changes, and new policies related to treatment for benefit in-kind and or enjoyments. This research was conducted with the aim of knowing the development of Tax Article 21 revenue during the COVID-19 pandemic in 2020 – 2022, the obstacles were faced by the Directorate General of Taxes in an effort to optimize Tax Article 21 revenue during the COVID-19 pandemic in 2020 – 2022 and the strategies undertaken to optimize Tax Article 21 revenue during the COVID-19 pandemic in 2020 – 2022. The method used in this research is descriptive qualitative analysis. The subjects in this research were employees at the Directorate of Tax Regulations II, and the Directorate of Potential, Compliance and Revenue. The results of this research show a decrease in revenue in 2020 and an increase in 2021 and 2022.